Value of Information in the Post-Truth Era - Dokić Mrša, Sanja (Sociološki godišnjak, 2023)
By reviewing the findings obtained thus far, this paper analyzes the impact of information and communication technologies (ICT) on the formation and availability of valuable informations. It is hypothesized that ICT has made the process of reaching valuable information easier and more difficult at the same time. By using scientific method of analysis, the overall goal of the study has been achieved, that is, a critical view of the role of ICT in having simultaneously accelerated and facilitated the formation, dissemination, and storage/availability of valuable information – but also led to unprecedented information disorder. By undermining people’s need to base decisions, attitudes, and opinions on valuable informations, the post-truth society erode one of the essential functions of the media, that is information.